Japan : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper analyzes macroeconomic developments and prospects for Japan during the 1990s. Following a surge in activity during 1996 and early 1997, the economy fell into recession in the second quarter of 1997. Real GDP fell by 3 3/4 percent during the four quarters ended March 1998; the unemployment rate reached historical highs; and deflationary pressures reemerged. The downturn was largely unexpected, and most forecasters had projected growth of about 2 percent in 1997. This paper also examines fiscal policy issues for Japan.